Nanotechnology: a law for Malaysia / Amir Amsyar Mohd Nazir, Yusof Mohamed Salleh and Zul Saddiqin Abdul Samad - Mohd Nazir, Amir Amsyar; Mohamed Salleh, Yusof; Abdul Samad, Zul Saddiqin (2014)
Today in 2014, the world has seen drastic development in technology. From day to day, month over month and year over year, there are many invention of new technology for the sake of improving the life of human being. Nanotechnology has become one of the greatest inventions where this technology has been said to become the future for this world. Nanotechnology had become widely use around the world including in Malaysia where we can see there is many Nano product had been sell around Malaysia such as washing machine, cosmetic products and even food. Notwithstanding, the thing which we concern the most is due the fact that the side effect of nanotechnology is uncertain. In this research we will discuss on why Malaysia need a specific law regarding nanotechnology. The first Chapter will contain the proposal of this research where it will cover on the problem statement, conceptual features, research question, research objective, literature review and scope of research. Next will be the Chapter 2. Under this chapter we will discuss on the history of nanotechnology itself. We will go into deeper on what is nanotechnology, who introduced nanotechnology and the benefits and potential benefits of nanotechnology. Furthermore we will discuss on why is it nanotechnology is said to become a future for the world. Then this chapter will also will cover on the Nano products across the globe and how wide it has been used in our daily life. Move on to the next chapter which is Chapter 3, this chapter will start cover on the adverse effect of nanotechnology itself. This chapter will also give a clear view on what is Nano toxicology apart from providing some Nano products which give adverse effect to human and environment. The discussion on the regulation of nanotechnology around the world will be cover in Chapter 4. Under this chapter we will go into the regulation of nanotechnology in developed countries such as European countries, United States of America, Australia and China. Furthermore we will discuss on the area that has been covered by the regulation such as industrial chemical, foods and feeds, and occupational health and safety. Lastly, this chapter will discuss a little bit on the loophole of the regulation itself. Finally, for the last chapter i.e. Chapter 5, we will conclude our research and put forward some recommendation towards how to treat the development of nanotechnology in Malaysia by having specific regulation on nanotechnology.